Are environmentally innovative companies inclined towards integrated environmental disclosure policies? - Isabel-María García-Sánchez; Nicola Raimo; Filippo Vitolla (Administrative Sciences, 2021)
In recent years, the correct representation of environmental performance has become increasingly important. In light of this, in the academic field, numerous researchers have examined the level and quality of environmental disclosure. However, in the context of studies relating to the determinants of environmental disclosure, little attention has been paid to the role of environmental innovation. This study, in the context of voluntary disclosure theory, aims to fill this important gap through the analysis of the impact of environmental innovation on the level of integrated environmental information disclosed by companies and the analysis of environmental performance as a mediating factor in this relationship. The results show a positive relationship between environmental innovation and integrated environmental disclosure. In addition, they show that environmental performance represents a mediating factor in this relationship. However, complementary analyses show that responsible firms adopt silent strategies in their environmental integrated disclosure policies in order to limit the knowledge by external users of the different environmental actions implemented.
Keywords: 350; environmental disclosure; environmental innovation; environmental performance; voluntary disclosure theory